MEN’S ROLE IN FAMILY PLANNING DECISION-MAKING IN DUTSE LOCAL GOVERNMENT AREA, JIGAWA STATE NIGERIA - Abdulkadir, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this paper is to assess men’s role in family planning (FP) decision-making, awareness, attitude, and practice of modern method in Dutse Local Government Area of Jigawa State. A total of 402 copies of questionnaires were administered using multi stage sampling technique. Data were analyzed descriptive and multiple logistic regression. 89% of men approved of the use of family planning while only about 11% disapproved of it. 80%of men had ever used contraception while 564 of them were current users. Spousal communication about family planning and other family reproductive goals was very poor. The socio-demographic correlates of men’s opinions included religion, marriage type, educational attainment, and occupation (p<0.05). Family planning programmes in northern Nigeria should focus on Muslim men Religions leaders should be involved in clarifying misconceptions on issues regarding family planning.